Laser Control of Self-Organization Process in Microscopic Region and Fabrication of Fine Microporous Structure. (25th October 2011) - Matsumura Matsumura, Yukimasa Yukimasa; Inami Inami, Wataru Wataru; Kawata Kawata, Yoshimasa Yoshimasa
Abstract : We present a controlling technique of microporous structure by laser irradiation during self-organization process. Self-organization process is fabrication method of microstructure. Polymer solution was dropped on the substrate at high humid condition. Water in air appears dropping air temperature below the dew point. The honeycomb structure with regularly aligned pores on the film was fabricated by attaching water droplets onto the solution surface. We demonstrate that it was possible to prevent forming pores at the region of laser irradiation and flat surface was fabricated. We also demonstrated that a combination structure with two pore sizes and flat surface was produced by a single laser-pulse irradiation. Our method is a unique microfabrication processing technique that combines the advantages of bottom-up and top-down techniques. This method is a promising technique that can be applied to produce for photonic crystals, biological cell culturing, surface science and electronics fields, and so forth.